2012
DOI: 10.1007/s00420-012-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

Does job satisfaction predict early return to work after coronary angioplasty or cardiac surgery?

Abstract: To the best of our knowledge, this is the first prospective study that investigated whether job satisfaction predicts time to RTW after cardiac interventions. The results suggested that when patients are satisfied with their job and positively perceived their work environment, they will be more likely to early RTW, independently of socio-demographic, medical and psychological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 50 publications
1
35
1
Order By: Relevance
“…The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16]. Other studies have shown that depression is common among cardiac patients and that it increases the risk for not resuming the job as well as the risk of longer time for RTW [3,9,39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16]. Other studies have shown that depression is common among cardiac patients and that it increases the risk for not resuming the job as well as the risk of longer time for RTW [3,9,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the health-related qua lity of life (HRQL) after cardiac interventions [10][11][12][13]. Most of these studies have found that predictors of HRQL after a heart surgery or coronary angioplasty were primarily psychological and not related to the illness severity [13][14][15][16]. Instead, research on professional life and work reintegration after cardiac interventions have focused mainly on the identification of factors predicting RTW (i.e., working/not working) or time for RTW [3,4,[17][18][19], while very few studies have investigated the quality of work resumption, in terms of a patient's job satisfaction and re-adaptation to work [15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations